2013
DOI: 10.4049/jimmunol.1300187
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human IL-15 Trans-Presentation by B Leukemic Cells from Chronic Lymphocytic Leukemia Induces Autologous NK Cell Proliferation Leading to Improved Anti-CD20 Immunotherapy

Abstract: Recombinant human IL-15 (rhIL-15) is one of the most promising cytokines for antitumor immunotherapy. In physiology IL-15 trans-presentation by accessory cells leads to pleiotropic activities, including activation of immune cells, such as NK cells. NK cells are largely involved in Ab-dependent cellular cytotoxicity mediated by therapeutic mAbs, such as rituximab, in chronic lymphocytic leukemia (CLL). Nevertheless, in CLL, Ab-dependent cellular cytotoxicity is relatively impaired by the low E:T ratio (NK/B leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 48 publications
(58 reference statements)
1
26
0
Order By: Relevance
“…However, the different experimental conditions used in the two studies (30 min ADCP, E:T ratio of 1:5 in Rafiq et al versus 4 h ADCP, E:T ratio of 3:1 in the current study) and differences in phagocytic effector cells (monocytes and MDMs derived from patients with CLL in Rafiq et al versus CD16 + /CD16 2 monocytes and M1/M2c macrophages in the current study) might have led to different results. Importantly, the elimination of leukemic B cells in whole blood from patients with CLL is consistently superior with GA101 (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…However, the different experimental conditions used in the two studies (30 min ADCP, E:T ratio of 1:5 in Rafiq et al versus 4 h ADCP, E:T ratio of 3:1 in the current study) and differences in phagocytic effector cells (monocytes and MDMs derived from patients with CLL in Rafiq et al versus CD16 + /CD16 2 monocytes and M1/M2c macrophages in the current study) might have led to different results. Importantly, the elimination of leukemic B cells in whole blood from patients with CLL is consistently superior with GA101 (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…In CLL patients, high burden of malignant B cells in peripheral blood naturally reduces NK cell proportion and negatively affects the natural and antibody-dependent cytotoxicity of the latter. 3,12 Laprevotte et al reported the median NK:B cells ratio as 0.02:1 in CLL patients and further showed that IL-15 could expand patients' NK cells, which in turn elevated CLL cell depletion by anti-CD20 antibodies (Rituximab and GA101). 12 To check whether increasing NK: B cells ratio also enhances the killing activity of the immunoligand, we purified NK cells from both patients 3 and 4 and incubated with purified CLL cells in autologous setting.…”
Section: Discussionmentioning
confidence: 99%
“…3,12 Laprevotte et al reported the median NK:B cells ratio as 0.02:1 in CLL patients and further showed that IL-15 could expand patients' NK cells, which in turn elevated CLL cell depletion by anti-CD20 antibodies (Rituximab and GA101). 12 To check whether increasing NK: B cells ratio also enhances the killing activity of the immunoligand, we purified NK cells from both patients 3 and 4 and incubated with purified CLL cells in autologous setting. Within 3 h of co-incubation, ULBP2-aCD19-aCD19 increased NK-cell-dependent killing of CLL cells from both patients in E:T-ratio-dependent manner while bypassing self-inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations